THE STRUGGLING OF WOMEN MASSAGERS IN NUSA DUA TOURISM AREA - Ni Desak Made Santi Diwyarthi (Jurnal Ilmiah Hospitality Management, 2018)
This research analyze women workers in informal sector, as massager in Nusa Dua tourism area. The research questions are the Strengths, Weaknesses, Opportunities and Threats faced by women workers in informal sector in Nusa Dua tourism area. This research is Quantitative Research by using  SWOT Analysis Technique. The results shows Internal and External Factors from women worker in informal sector. The Internal factors are Strength and Weakness, and External factors are Opportunity and Threat. Internal Factors are Strength: Balinese women are known to be friendly and courteous, Female massagers on the beaches of Nusa Dua tourism area are competent human resources in the field of tourism because of experienced and well trained.  Weakness: Trip to Nusa Dua that sometimes takes a long time because of traffic jam, Great influenced by weather change factors, Boredom and no career development opportunities for women massagers. External Factors are  Opportunity: Opportunities to participate actively in tourism, Improve the experience in tourism, Opportunity to interact with various cultural aspects from outside in open knowledge insight.  Threath: Increasing number of other tourist destinations that make more and more destination for tourists, The offer of an existing Social Culture attraction keeps visiting tourists who can feel bored and no longer interested in the offer. Keywords: Struggling, Women, Massagers, Tourism